Translation Ability and Its Influential Factors of English Club Students in Debate Class - Tanti Nur Khasanah; Imroatus Solikhah (ELE Reviews: English Language Education Reviews, 2022)
Translation is considered an essential element in the process of English learning. This descriptive qualitative study explores the translation ability and its influential factors performed by nine English club students of SMK Negeri 2 Surakarta in their debate class. Data were obtained by conducting a translation test. The students answered a questionnaire tested by the KR-20 formula to acknowledge the factors deeply. The results reveal that their ability to translate texts was good and excellent. Also, by using Microsoft Excel and interpreting using various theories in ELT, it was found that their ability was influenced by not only the external, internal, and individual factors but also their general learning strategies, way of learning vocabulary, teachers’ strategies in teaching grammar, and online tools as the part of learning media utilized by them. As translation becomes an inevitable process in ELT, these findings provide theoretical evidence that conducting TEFL by being attentive to the potential factors above and emphasizing the instructional designs is crucial. In addition, they directly influence the EFL learners’ translation ability, reflecting their English mastery and determining their success in the language learning process. Further, EFL teachers should pay more attention to their teaching strategy, consider allowing students access to online tools and motivate them to have a proper learning environment and reach optimal learning outcomes.